Penegakan Hukum Terhadap Pelaku Tindak Pidana Video Deepfake Porn Dihubungkan Hukum Pidana Postif Di Indonesia: - Antika Setia Dewi; Setiawan, Dian Alan (UNISBA Press, 2024)
ABSTRACT- The development of technology and information has affected many aspects of social life, The development of technology and information is characterized by the emergence of interconnected networks. The internet certainly helps people to facilitate work and other activities. However, with the development of technology and information, there are also growing types of crime in the field, one of which is cybercrime. Cybercrime can be explained as one of the unlawful activities or illegal activities using computer technology carried out through electronic information networks or the internet. One form of cybercrime is the distribution of pornographic content through social media and internet networks, which is then known as cyber pornography. One form of technological advancement that can facilitate engineering is deepfake, which is a technique using artificial intelligence (AI) that can change a person's face in a video. So this research aims to find out how law enforcement on cases that occur due to the criminal act of making and distributing deepfake videos. The factor causing the spread of deepfake porn videos through social media is the perpetrator's personal hatred of public figures or celebrities. As well as law enforcement against the perpetrators of deepfake porn videos in Indonesia, has not been running effectively. This is caused by several factors, namely legal factors, technological factors and also the law enforcement factor itself. So it is necessary to pay attention to special law enforcement regarding the offense of spreading deepfake porn videos. ABSTRAK- Perkembangan teknologi dan informasi terjadi mempengaruhi banyak aspek dalam kehidupan bersosial, Perkembangan teknologi dan informasi ditandai dengan munculnya internet. Internet tentu membantu masyarakat untuk mempermudah pekerjaan maupun kegiatan lainnya. Namun, dengan adanya perkembangan teknologi dan informasi, semakin berkembang juga jenis kejahatan dalam bidangnya, salah satunya adalah kejahatan siber. Kejahatan siber dapat dijelaskan sebagai salah satu kegiatan melanggar hukum atau kegiatan ilegal menggunakan teknologi komputer yang dilakukan melalui jaringan informasi elektronik atau internet. Salah satu bentuk dari kejahatan siber adalah penyebaran konten pornografi melalui media sosial dan jejaring internet, yang kemudian dikenal dengan pornografi siber. Salah satu bentuk kemajuan teknologi yang dapat mempermudah perekayasaan yaitu deepfake yang merupakan teknik menggunakan kecerdasan buatan atau artifical intelligence (AI) yang mampu mengubah wajah seseorang dalam video. Faktor penyebab penyebaran video deepfake porn melalui media sosial adalah kebencian pribadi pelaku terhadap tokoh publik atau selebriti. Serta penegakan hukum terhadap pelaku video deepfake porn di Indonesia, belum berjalan secara efektif. Hal ini disebabkan oleh beberapa faktor yaitu faktor hukum, faktor teknologi dan juga faktor penegak hukum itu sendiri. Maka perlu diperhatikan penegakan hukum khusus mengenai pelanggaran penyebaran video deepfake porn.